Table olives from Portugal: phenolic compounds, antioxidant potential and antimicrobial activity - Pereira, J.A. (2008)
The phenolic compounds composition, antioxidant potential, and antimicrobial activity of different table olives from Portugal, namely, natural black olives “Galega”, black ripe olive “Negrinha de Freixo”, Protected Designation of Origin (PDO) “Azeitona de Conserva Negrinha de Freixo” olives, and “Azeitona de Conserva de Elvas e Campo Maior” Designation of Origin (DO) olives, were investigated. The analysis of phenolic compounds was performed by reversed-phase HPLC/DAD, and seven compounds were identified and quantified: hydroxytyrosol, tyrosol, 5- O-caffeoilquinic acid, verbascoside, luteolin 7-O-glucoside, rutin, and luteolin. The antioxidant activity was assessed by the reducing power assay, the scavenging effect on DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals, and the â-carotene linoleate model system. The antioxidant activity was correlated with the amount of phenolics found in each sample. The antimicrobial activity was screened using Gram-positive ( Bacillus cereus, Bacillus subtilis, Staphylococcus aureus) and Gram-negative bacteria ( Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae) and fungi ( Candida albicans, Cryptococcus neoformans). PDO and DO table olives revealed a wide range of antimicrobial activity. C. albicanswas resistant to all the analyzed extracts.